Technological choices under uncertainty: Does organizational aspiration matter? - Dong, John Qi (Strategic management journal, 2021)
Research Summary The behavioral theory of the firm suggests that organizations make strategic choices to retain or search for a technology based on performance feedback in comparison to organizational aspiration. Such technological choices become challenging as decision makers face uncertainty not only in technological search, but also from technology deterioration and market turbulence. While different organizational aspirations have been used in prior research, their performance and risk implications for technological choices are unclear. I advance theory by conducting a simulation study to systematically investigate the performance and risk of technological choices with different organizational aspirations, and explore their contingencies on technological and market uncertainty. The simulation results provide novel insights into the indispensable role of goal setting to ascertain organizational performance. Managerial Summary Goal setting has important impacts on the performance and risk of strategic decisions. While it is often believed that processing more information can help managers cope with uncertainty, this study shows that paying attention to both internal and external performance goals may be suboptimal for technological choices. Solely relying on an internal performance goal may even do more harm than good. A superior way of goal setting is to focus on external performance information from a reasonable reference group, such as firms with a similar performance or all industry peers rather than the best‐in‐class in the industry. This is more beneficial when technologies rapidly change and is less useful when customer preferences shift due to unpredictable shocks (e.g., the COVID‐19 pandemic).